2012
DOI: 10.1002/star.201200129
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic response in healthy rats fed with composite cereal bars

Abstract: Three composite cereal bars containing white maize, blue maize, or unripe banana flours were prepared. The glycemic response in rats feed with a dose available carbohydrates, and the bars effect on a glucose tolerance test were evaluated. A dose of 0.85 g/kg was used in the experiments with the three bars. The experiment with a glucose load showed that rats previously fed with blue maize and unripe banana bars showed reduced glycemic response, probably as consequence of glucose entrapment within the food matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As rats exercise, blood glucose levels are influenced by the presence or absence of carbohydrate intake. Several studies have shown that mice given glucose-type carbohydrate supplementation before exercise, have peak blood glucose levels at 45-60 minutes 15,16 . Another method in the same study showed rats given carbohydrates supplementation peaked at 15 minutes after supplementation 16 .…”
Section: Effect Of Brown Sugarcane Supplementation On Blood Glucose O...mentioning
confidence: 99%
“…As rats exercise, blood glucose levels are influenced by the presence or absence of carbohydrate intake. Several studies have shown that mice given glucose-type carbohydrate supplementation before exercise, have peak blood glucose levels at 45-60 minutes 15,16 . Another method in the same study showed rats given carbohydrates supplementation peaked at 15 minutes after supplementation 16 .…”
Section: Effect Of Brown Sugarcane Supplementation On Blood Glucose O...mentioning
confidence: 99%
“…Dietary fibers have been associated with improved postprandial glucose and insulin responses. There are many studies investigating the reduction of postprandial glucose responses after fiber-rich meal consumption (Fotschki et al 2014;Grover et al 2011;Utrilla-Coello et al 2013). The postprandial glucose reducing effect of soluble fibers is due to the gel forming ability of soluble fibers (Cassidy et al 2018).…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…), a tropical fruit, is widely cultivated. Green bananas (Musa paradisiaca L.) are rich of starch (20-25%) in the pulp of the fruits (Cordenunsi and Lajolo, 1995) which can be utilized as banana flour combining into food products (Juarez-Garcia et al, 2006;Aparicio-Saguilan et al, 2007;Hernández-Nava et al, 2009;Utrilla-Coello et al, 2013;Flores-Silva et al, 2017;Khoozani et al, 2020). High fiber and slowly digestible starch contents in banana flour can sustain glucose release which will reduce insulin response, maintain satiety level, control energy intake (Aller et al, 2011), and decrease absorption of macronutrients (Dayib et al, 2020).…”
Section: Introductionmentioning
confidence: 99%